Strategy of The Teacher in Applying The 2013 Curriculum to Students' Social Attitude - Ode, Muhamad Nur Intan (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The aims of this study are to determine the strategies used by teachers at State Elementary School 2 Wameo in developing students' social attitudes and to determine the factors that shape students' positive social attitudes. This research is a field study with a qualitative method, with data collection through observation, interviews, and documentation. The research findings show that the teacher's strategy begins with an explanation of the value of skills and approaches with students, followed by the implementation of the 2013 curriculum as a whole, and finally the teacher fosters social attitudes by providing interesting learning in the classroom. The factors for the formation of students' social attitudes. Internally, the supporting factor is that students can understand social attitudes and teachers in presenting interesting learning in the classroom. The inhibiting factor is the family, such as the lack of parental attention and supervision of students at home.